1974
DOI: 10.1104/pp.53.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall and Protoplast Isoperoxidases in Relation to Injury, Indoleacetic Acid, and Ethylene Effects

Abstract: In tobacco (Nicotiana Tabacum) pith, sweet potato (Ipomnoea batatas), and carrot (Daucus carota) storage roots, differences were found between cell wall and protoplast peroxidases in their isoenzyme patterns, activity, and reaction to tissue injury.In the pith of elongating tobacco internodes, 90% of total activity was associated with the walls, 80% of which was due to the ionically and covalently bound fractions. With senescence, the increase in activity occurred mainly in the protoplast and the free fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

1975
1975
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…In addition, generalized soluble or wall-bound POD activity increases in other plant species in response to wounding (Birecka and Miller, 1974;Kawaoka et al, 1994), pathogens (Bashan et al, 1987), salicylic acid (Rao et al, 1997), and jasmonates (Thaler et al, 1996;Moore et al, 2003). While JA and insect wounding have been found to elevate total soluble POD activity similarly (Choi et al, 1994;Tamari et al, 1995;Zhang and Baldwin, 1997), this study is among the first to suggest that various peroxidase isozymes may be differentially responsive to JA or other signals (Buzi et al, 2004) and the first to find insectresponsive POD isoforms.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, generalized soluble or wall-bound POD activity increases in other plant species in response to wounding (Birecka and Miller, 1974;Kawaoka et al, 1994), pathogens (Bashan et al, 1987), salicylic acid (Rao et al, 1997), and jasmonates (Thaler et al, 1996;Moore et al, 2003). While JA and insect wounding have been found to elevate total soluble POD activity similarly (Choi et al, 1994;Tamari et al, 1995;Zhang and Baldwin, 1997), this study is among the first to suggest that various peroxidase isozymes may be differentially responsive to JA or other signals (Buzi et al, 2004) and the first to find insectresponsive POD isoforms.…”
Section: Discussionmentioning
confidence: 57%
“…Each plant species typically displays a unique pattern and number of soluble and wall-bound isozymes that may respond differentially to environmental stimuli. Some of the factors known to influence POD isozyme expression are mechanical wounding (Birecka and Miller, 1974;Svalheim and Robertsen, 1990), mite feeding (Bronner et al, 1991), pathogen infection (Lagrimini and Rothstein, 1987;Ye et al, 1990), plant hormones (Ridge and Osborne, 1970;Birecka and Miller, 1974;Neuman et al, 1992), and plant developmental stage (Pao and Morgan, 1988;Biles and Martyn, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures related to isolation of the protoplast and wall peroxidases were similar to those previously used (6). The Triton X-100 extracts showed traces or no peroxidase activity.…”
Section: Methodsmentioning
confidence: 92%
“…Previous study on Wisconsin 38 tobacco plant pith has shown a great increase of peroxidase activity, not only in its protoplast fraction, but also in the wall-bound fraction in response to cutting injury (6). Neither senescence nor injury caused qualitative changes in the cell isoperoxidase pattern.…”
mentioning
confidence: 99%